2016
DOI: 10.1128/msphere.00045-16
|View full text |Cite
|
Sign up to set email alerts
|

The Rhoptry Pseudokinase ROP54 Modulates Toxoplasma gondii Virulence and Host GBP2 Loading

Abstract: The interactions between intracellular microbes and their host cells can lead to the discovery of novel drug targets. During Toxoplasma infections, host cells express an array of immunity-related GTPases (IRGs) and guanylate binding proteins (GBPs) that load onto the parasite-containing vacuole to clear the parasite. To counter this mechanism, the parasite secretes effector proteins that traffic to the vacuole to disarm the immunity-related loading proteins and evade the immune response. While the interplay be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 56 publications
2
22
0
Order By: Relevance
“…1). ROP18 and ROP5 are also implicated in resistance to GBPs in mice (185), as is the pseudokinase ROP45 (230). The level of complexity exhibited by this set of parasite effectors speaks to the importance of thwarting the IRG and GBP host defense systems in mouse for the survival of T. gondii.…”
Section: Defining Pathogenesis Determinantsmentioning
confidence: 99%
“…1). ROP18 and ROP5 are also implicated in resistance to GBPs in mice (185), as is the pseudokinase ROP45 (230). The level of complexity exhibited by this set of parasite effectors speaks to the importance of thwarting the IRG and GBP host defense systems in mouse for the survival of T. gondii.…”
Section: Defining Pathogenesis Determinantsmentioning
confidence: 99%
“…These ROPKs are polymorphic and can account for much of the differences observed in the virulence of different T. gondii strains. Some ROPKs have been shown to play roles in T. gondii virulence, establishing chronic T. gondii infection and manipulating the host innate immune response (Saeij et al, 2006; Taylor et al, 2006; Behnke et al, 2011; Butcher et al, 2011; Reese et al, 2011; Hunter and Sibley, 2012; Camejo et al, 2014; Etheridge et al, 2014; Fox et al, 2016; Jones et al, 2016; Kim et al, 2016). For instance, ROP5, ROP17, and ROP18 forming ROP5/17/18 complex function as virulence factors to prevent immune related GTPases accumulation at the parasitophorous vacuole (PV) (Saeij et al, 2006; Taylor et al, 2006; Behnke et al, 2011; Reese et al, 2011; Etheridge et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, ROP5, ROP17, and ROP18 forming ROP5/17/18 complex function as virulence factors to prevent immune related GTPases accumulation at the parasitophorous vacuole (PV) (Saeij et al, 2006; Taylor et al, 2006; Behnke et al, 2011; Reese et al, 2011; Etheridge et al, 2014). ROP54, a type II T. gondii virulence factor, modulates the innate immune loading of GTP-binding protein 2, which does not act by interacting with the ROP5/17/18 complex (Kim et al, 2016). ROP16 can inhibit the production of the IL-12 in a parasite strain type dependent manner via activation of the host transcription factors STAT3 and STAT6 (Butcher et al, 2011) and can mediate human neuroblastoma SH-SY5Y apoptosis and cell cycle arrest in G1 phase by affecting the expression of Bax/Bcl-2 and p21/CDKs (Chang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…T. gondii control requires a fine-tuning induction of pro-inflammatory and anti-inflammatory cytokines, such as IL-12, IFN-γ, and IL-10 (Gazzinelli et al, 1991, 1996), but the tachyzoite stage of the parasite is able to subvert the immune response, being able, for instance, to blockade NF-κB nuclear translocation and actively interfere in the IL-12 production (Yarovinsky, 2014; Kim et al, 2016). Previous studies have been shown the ability of ScLL and ArtinM to induce the production of cytokines, when used as immunological adjuvants in vaccination protocols (Cardoso et al, 2011, 2012).…”
Section: Discussionmentioning
confidence: 99%